Mutant KIT as imatinib-sensitive target in metastatic sinonasal carcinoma - Dieter, Sebastian M.; Heining, Christoph; Hübschmann, Daniel; Hutter, Barbara; Ehrenberg, Karl Roland; Fröhlich, Martina; Scholl, Claudia; Mavratzas, Athanasios; Jung, Carla Sabine; Gröschel, Stefan; Kalle, Christof von; Eils, Roland; et al. (Annals of oncology, 2017)
AbstractBackground. Sinonasal carcinomas (SNCs) comprise various rare tumor types that are characterized by marked histologic diversity and largely unknown mol
Published online 29 September 2016
Gesehen am 23.10.2018